Understanding computers today and tomorrow - Parker, Charles S. 1945- (Dryden Press, 2000)
Understanding Computers has been written and designed to make use of the Internet's power. Throughout each chapter users will find "Web Tutor" icons in the margins directing them to the Parker web site for multimedia-enhanced tutorials. "Further Exploration" icons point to articles and sites with more in-depth information on a given topic.